2022
DOI: 10.1093/cid/ciac284
|View full text |Cite|
|
Sign up to set email alerts
|

Initiating Intramuscular Depot Medroxyprogesterone Acetate Increases Frequencies of Th17-like Human Immunodeficiency Virus Target Cells in the Genital Tract of Women in South Africa: A Randomized Trial

Abstract: Background Cervicovaginal CD4+ T cells are preferential targets for human immunodeficiency virus (HIV) infection and have consequently been used as a proxy measure for HIV susceptibility. The ECHO randomized trial offered a unique opportunity to consider the association between contraceptives and Th17-like cells within a trial designed to evaluate HIV risk. In a mucosal substudy of the ECHO trial, we compared the impact of initiating intramuscular depot medroxyprogesterone acetate (DMPA-IM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…From those who enrolled in this mucosal sub-study, sample size calculations indicated that 20 participants per randomized arm per site with complete sample sets at all three timepoints were needed, and thus we randomly selected women who met this criterion at the Johannesburg, South Africa and Kisumu, Kenya sites. However, at the Cape Town, South Africa site, cervical cytobrushes from 80 consecutively enrolled women were processed for phenotyping ex vivo at enrollment and 1 month post-contraception initiation for a separate study 56 , and we elected to include all of these participants, rather than a random subset. In addition, participants that were included in the secondary (case-control) analysis but also had samples available at enrollment, 1 month, and 6 months, were added to the pre-post analysis group if not already included.…”
Section: Methodsmentioning
confidence: 99%
“…From those who enrolled in this mucosal sub-study, sample size calculations indicated that 20 participants per randomized arm per site with complete sample sets at all three timepoints were needed, and thus we randomly selected women who met this criterion at the Johannesburg, South Africa and Kisumu, Kenya sites. However, at the Cape Town, South Africa site, cervical cytobrushes from 80 consecutively enrolled women were processed for phenotyping ex vivo at enrollment and 1 month post-contraception initiation for a separate study 56 , and we elected to include all of these participants, rather than a random subset. In addition, participants that were included in the secondary (case-control) analysis but also had samples available at enrollment, 1 month, and 6 months, were added to the pre-post analysis group if not already included.…”
Section: Methodsmentioning
confidence: 99%